Democratization in China, Korea and Southeast Asia? local and national perspectives - White, Lynn T. III 1941- (Politics in Asia series, 2014)
"Rapid economic pluralization in East Asia has empowered local and medial groups, and with this change comes the need to radically rethink usual notions regarding the ways in which 'democracies' emerge or 'citizens' gain more power. This book demonstrates how careful examinations of current developments in East Asia indicate a need for major expansion of our understandings of democracy and democratization, and challenges the traditional way in which political regimes are conceived and labelled. Further, it shows from Asian experiences that democracy and its precursors come in more forms than most liberals have yet imagined. In reviewing the experiences of states across East Asia, this book shows that actual democracies and ostensible democratizations in Asia are less like those in the West than the surprisingly consensual standard political science of democratization suggests. It first examines the extreme variation of democracy's meaning in many Asian states that hold contested elections (South Korea, Taiwan, Indonesia, Malaysia, the Philippines, and Thailand), and in turn shifts its attention to China. It analyses a range of grassroots forces driving political change in the PRC, and uncovers both accelerators and brakes on China's political reform process. Importantly, the contributors show that models for China's political future exist both outside the PRC, including in other East Asian states, and within China, in localities and sectors that already are pushing the boundaries of the powerful, but no longer all-powerful, PRC party-state"--Provided by publisher.